الاسلام في داغستان (Al-Islam fi Dagestan) - Kamilov Askhabali,; Mudasir Rosder ,; Abdul Rahman Mahmood, (Penerbit Universiti Kebangsaan Malaysia, 2012)
The historians agree that the first Islamic conquest to Caucas was in 639M, but the spread of Islam was slow for many reasons. The most important of which is the difficult nature of the Caucas mountains. The altitude of the Caucas mauntain may reach than five thousand meters. This was unknown by the Arabs who have only much experiences in fighting on the ground and the flat desert. Since the first day of existence of Islam in the area, Islamic religion brought more impact on the Dagestnian people compared to the impact of any of other religions and philosophies. Islamic influence lies in its principles of high code of ethics. Islamic religion has influenced Dagestan not as equally as the Middle East countries or even the other countries in the world, becouse of Dagestnian people were influenced by the atheistic belief before this, that is the communist ideology, which classifies religion to be similar as culture and education.